2015
DOI: 10.1016/j.ijid.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma is involved in apoptosis of trophoblast cells at the maternal–fetal interface following Toxoplasma gondii infection

Abstract: The levels of IFN-γ secreted by dNK cells at the maternal-fetal interface were closely correlated with the apoptosis of trophoblasts upon T. gondii infection. The apoptosis of trophoblasts induced by the increase in IFN-γ depended on the caspase pathway, which may contribute to the abnormal pregnancy outcomes that occur with T. gondii infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 34 publications
2
31
1
4
Order By: Relevance
“…Then, the local immune cells are the major source of IFNG in the maternal-fetal interface because the decidual natural killer cells, and consequently the trophoblast cells, are stimulated by IFNG in a paracrine manner. Decidual natural killer cells cocultured with trophoblast produce from 20 to 30 ng/ml IFNG, and this production increases significantly when these cells are infected by T. gondii (;80 ng/ml) [81]. Therefore, the IFNG concentrations used in our present study are similar to those found during in vivo conditions.…”
Section: Discussionsupporting
confidence: 79%
“…Then, the local immune cells are the major source of IFNG in the maternal-fetal interface because the decidual natural killer cells, and consequently the trophoblast cells, are stimulated by IFNG in a paracrine manner. Decidual natural killer cells cocultured with trophoblast produce from 20 to 30 ng/ml IFNG, and this production increases significantly when these cells are infected by T. gondii (;80 ng/ml) [81]. Therefore, the IFNG concentrations used in our present study are similar to those found during in vivo conditions.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that activated caspase 8 and caspase 3 expressions are significantly upregulated in the T . gondii ‐infected trophoblasts . Therefore, in the T .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 It has been shown that activated caspase 8 and caspase 3 expressions are significantly upregulated in the T. gondiiinfected trophoblasts. 30 Therefore, in the T. gondii-induced apoptosis of trophoblasts, Fas ligand-caspase pathway is considered as a major pathway. In vitro TNF-alpha expression in macrophage cell lines has been shown to play a major role in host resistance against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although infection of T. gondii is frequently asymptomatic and self-limiting in nonpregnant individuals, infection in pregnant individuals causes miscarriage, spontaneous abortion, and fetal teratogenesis especially in the early stage of pregnancy. 2 The typical clinical alteration of fetal teratogenesis caused by toxoplasmosis includes chorioretinitis 3 and microcephalia. 4 Previous reports have documented that fetal teratogenesis may be mainly due to immunopathological effects triggered by T. gondii antigens rather than the proliferation of itself at maternal-fetal interface.…”
Section: Introductionmentioning
confidence: 99%